Role of non-descent vaginal hysterectomy in previous cesarean section scar women - Kumar, Naina; Tayade, Surekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Non Descent Vaginal Hysterectomy (NDVH) is removal of uterus through vagina in absence of cervical descent. Objective: To assess safety, feasibility of NDVH in patients with previous cesarean section. Methods: Prospective study was conducted at department of Obstetrics and Gynecology of rural Tertiary care centre of Central India from January 2013 to December 2014. Effort was made to perform hysterectomies vaginally in women with benign conditions in absence of prolapsed uterus with history of one, two or three cesarean sections. Women with adnexal masses, endometriosis/big uterus (>16 weeks) were excluded from study. Information regarding age, parity, uterine size, blood loss, duration of operation, difficulties in separating bladder, intra-operative, post-operative complications, hospital stay were recorded. Results: Total ten cases were selected for NDVH with history of one, two/ three cesarean sections. All successfully underwent NDVH, except one in which bladder injury occurred which was repaired at same time from below. Five patients had previous one Lower Segment Cesarean Section (LSCS), four had two LSCS and one had three LSCS. Commonest indication was leiomyoma of uterus followed by abnormal uterine bleeding. Mean duration of surgery was 50 ± 20.5 min. Mean blood loss was 150 ± 65 ml. Post-operative complications were minimal with no scar, patient mobility, resumption of daily activities was fast. Mean hospital stay was 4-5 days. Conclusions: Vaginal hysterectomy appears to be safe, cost effective alternative to abdominal hysterectomy in women with previous cesarean section scar requiring hysterectomy for benign conditions with fewer complications, shorter hospital stay.